Establishment of Kogabwilhan in Supporting the Defense Area’s Resilience - Ading Priyotantoko; Armaidy Armawi; Bayu Dardias Kurniadi; Darto Wahidin (Future Science, 2021)
In the past, defense in warfare was carried out conventionally by using weapons. Now the defense system has shifted to modern types of warfare, either through culture, diplomacy, technology, and ideology. Kogabwilhan as a unit directly under the President’s command. The TNI’s Kogabwilhan is a representation of the concept of TNI's interoperability capability which is currently a priority policy for TNI Commanders. Kogabwilhan was established as an effort of the TNI to carry out the strengthening of resilience and deterrence against various potential threats, both from outside and within the country. The presence of the Kogabwilhan is a form of TNI's preparedness in handling the crisis. The development of defense areas is directed at maintaining the natural potential and social conditions that exist in the territory of Indonesia. Kogabwilhan is here to coordinate with various parties to maintain all aspects, both disaster mitigation, regional development, welfare, and regional defense. The government determined the domicile of MaKogabwilhan II in Balikpapan, East Kalimantan Province. The determination must have taken into account some aspects of the current command, control, strategy, and infrastructure. Thus, the formation of the Kogabwilhan has a strategic role in maintaining the sovereignty of the Indonesian state. The formation of the Kogabwilhan was carried out as one of the steps taken by the TNI to strengthen Its deterrence against various potential threats from outside and within the country. However, there are three things that have an impact on the resilience of the defense area as a result of the formation of Kogabwilhan II in Balikpapan. First, the military managerial role. The improvement of military managerial capabilities must be based on good planning, organization, implementation arrangements, and supervision, so that they can be controlled optimally. Second, the role of legal policy. Kogabwilhan must be able to enforce the law, both on land, sea, and air. Third, the role of diplomacy. The establishment of Kogabwilhan could reduce existing conflicts, so diplomacy skills are very important to have. Therefore, the development of defense and security in strategic areas is currently increasingly complex and escalating in various parts of the world.